2014
DOI: 10.18632/oncotarget.2966
|View full text |Cite
|
Sign up to set email alerts
|

Chloride channel-3 promotes tumor metastasis by regulating membrane ruffling and is associated with poor survival

Abstract: The chloride channel-3 (ClC-3) protein is known to be a component of Cl− channels involved in cell volume regulation or acidification of intracellular vesicles. Here, we report that ClC-3 was highly expressed in the cytoplasm of metastatic carcinomatous cells and accelerated cell migration in vitro and tumor metastasis in vivo. High-grade expression of cytoplasmic ClC-3 predicted poor survival in cancer patients. We found that independent of its volume-activated Cl− channel properties, ClC-3 was able to promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…ClC-3, a member of the voltage-gated chloride channel family, shows the properties of cell cycle-dependent expression and subcellular distribution, and plays an important role in the regulation of cell proliferation, migration and apoptosis, especially in cancerous cells (Hong et al, 2015;Liu et al, 2013;Mao et al, 2012Mao et al, , 2013Xu et al, 2014;Zhang et al, 2013a). The inducible ClC-3 gene deletion eliminating native VRAC in adult mice overwhelmingly suggested that ClC-3 is a key component of native VRAC in mammalian heart, not in the brain (Xiong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ClC-3, a member of the voltage-gated chloride channel family, shows the properties of cell cycle-dependent expression and subcellular distribution, and plays an important role in the regulation of cell proliferation, migration and apoptosis, especially in cancerous cells (Hong et al, 2015;Liu et al, 2013;Mao et al, 2012Mao et al, , 2013Xu et al, 2014;Zhang et al, 2013a). The inducible ClC-3 gene deletion eliminating native VRAC in adult mice overwhelmingly suggested that ClC-3 is a key component of native VRAC in mammalian heart, not in the brain (Xiong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our and other labs have demonstrated that ClC‐3 is a candidate of the channel protein mediating volume‐activated Cl − currents (Xu et al, ; Zhu et al, ). The above results indicated that the properties of 17β‐E2‐activated Cl − currents were similar to the volume‐activated Cl − currents.…”
Section: Resultsmentioning
confidence: 84%
“…In MDA‐MB‐453 cells, siRNA‐mediated inhibition of ClC‐3 Cl − /H + transporter exerted transcriptional repression of HER2 (Figure ). ANO1 and ClC‐3 both promote tumor metastasis and are associated with a poor prognosis . ANO1 proteins are localized at the plasma membrane and regulate membrane potential, whereas ClC‐3 proteins are distributed among intracellular organelles such as endosomes and lysosomes, and are involved in vesicular acidification and Cl − accumulation as a Cl − /H + transporter .…”
Section: Discussionmentioning
confidence: 99%
“…ANO1 and ClC-3 both promote tumor metastasis and are associated with a poor prognosis. 6,29 ANO1 proteins are localized at the plasma membrane and regulate membrane potential, 30 whereas ClC-3 proteins are distributed among intracellular organelles such as endosomes and lysosomes, and are involved in vesicular acidification and Cl − accumulation as a Cl − /H + transporter. 2,31 As shown in Figure 3 6B); however, the siRNA-mediated inhibition of CLIC1 did not repress HER2 transcription in either cell (Figures 2A and 6C).…”
Section: Discussionmentioning
confidence: 99%